DAERAH BAHAYA BANJIR DI SUB DAERAH ALIRAN SUNGAI SEPAUK DAN TEMPUNAK, KABUPATEN SINTANG, PROVINSI KALIMANTAN BARAT (Flood hazard in Sepauk and Tempunak Sub Watersheds, Sintang Regency, West Kalimantan Province) - Diah Auliyani (Jurnal Penelitian Pengelolaan Daerah Aliran Sungai (Journal of Watershed Management Research), 2017)
Flood-prone areas mapping is often constrained by limited data availability at the site level. A quick assessment of sub watershed degradation method can be used to identify the degradation level of a sub watershed includes the flood hazard areas. This method is very easy to be applied at a site level using Geographic Information System (GIS), although it has minimum data. The aim of this study was to analyze the level of flood hazard in Sepauk and Tempunak Sub Watersheds, Sintang Regency, West Kalimantan Province. The required data were DEM/ SRTM (Digital Elevation Model/ Shuttle Radar Topography Mission), daily rainfall, and land cover. Quick assessment of sub watershed degradation method was applied to classify the flood-prone level of the study areas. The results showed that most of the study areas were categorized as high level of flood hazard (78% for Sepauk and 56% for Tempunak). The land covers of those areas were dominated by mixed dryland agriculture, bare land, and settlements. In addition, high level of flood hazard areas in Sepauk Sub Watershed was also affected by the existence of mining and dryland agriculture areas. Since the land cover change is a dynamic process, the flood hazard areas mapping should also be adjusted continuously to minimize the flood impact.